Tunisia Monetary Policy Since the Arab Spring : The Fall of the Exchange Rate Anchor and Rise of Inflation Targeting - End, Nicolas (IMF Working Papers; Working Paper, 2020)
In this paper, we argue that inflation targeting could be the future of Tunisia's monetary policy. Monetary targeting has proven to be ineffective due to the composition of reserve money, structural liquidity deficit, and higher instability of the money multiplier after 2010. Exchange rate targeting is no longer feasible due to the level of international reserves, current account deficit, and inflation differentials with main trading partners. The Central Bank of Tunisia has already made important progress toward inflation targeting. The paper evidences the existence of increasingly effective interest rate transmission as well as the changing exchange rate passthrough to inflation with the gradual move toward further exchange rate flexibility.